2019
DOI: 10.1002/jcp.28344
|View full text |Cite
|
Sign up to set email alerts
|

KCNQ1OT1 affects the progression of diabetic retinopathy by regulating miR‐1470 and epidermal growth factor receptor

Abstract: Long noncoding RNAs have been reported to play important roles in the pathogenesis of diabetic retinopathy (DR), which has been considered as the most common disease leading to vision loss. However, it is still unclear whether KCNQ1 overlapping transcript 1 (KCNQ1OT1) could affect DR. In this study, regarding quantitative reverse transcription polymerase chain reaction assay, KCNQ1OT1 level was upregulated while microRNA‐1470 (miR‐1470) was decreased in DR patients and human retinal endothelial cells. High KCN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 33 publications
0
27
0
Order By: Relevance
“…Recent studies have con rmed that KCNQ1OT1 plays a vital role in diabetic complications, such as diabetic cardiomyopathy[6], diabetic nephropathy[8], and diabetic ocular disease [9,17]. KCNQ1OT1 and NLRP3 in ammasome are triggered in the corneal endothelium of diabetic patients and mice, as well as in HG-treated corneal endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have con rmed that KCNQ1OT1 plays a vital role in diabetic complications, such as diabetic cardiomyopathy[6], diabetic nephropathy[8], and diabetic ocular disease [9,17]. KCNQ1OT1 and NLRP3 in ammasome are triggered in the corneal endothelium of diabetic patients and mice, as well as in HG-treated corneal endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of KCNQ1OT1 is elevated in HG-treated human retinal endothelial cells (hRECs) and in the aqueous humor of patients with DR compared with the normal control group. KCNQ1OT1 promotes DR progression by the regulation of miR-1470 and epidermal growth factor receptor (EGFR) [17]. However, whether KCNQ1OT1 is involved in regulating NLRP3 in ammasome activation of Müller cells in DR remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…36 Additionally, it is reported that KCNQ1OT1 accelerates the development of diabetic retinopathy by targeting miR-1470. 37 We supposed that KCNQ1OT1 might also be a ceRNA, so we worked out XIAP is a modulator in cell viability, apoptosis, and inflammatory responses. For example, studies have demonstrated that CCN1 promoted FasL-induced apoptosis of H9c2 cardiomyocytes by disrupting XIAP.…”
Section: Discussionmentioning
confidence: 99%
“…LncRNAs play significant roles in modulating mRNA stability, functioning as miRNA sponges that compete for endogenous RNAs. 25,26 To further explore whether specific miRNAs are sponged by KCNQ1OT1, we identified miRNAs that were differentially expressed between intact control bone and postfracture calluses in a mouse model of fracture healing. Based on searches of the GEO database, we selected miR-701-3p.…”
Section: Discussionmentioning
confidence: 99%